Management of Sea Turtle in the Beach of Alas Purwo National Park, the Province of East Java - Suharso .; Agus Priyono; Mirza D Kusrini (Department of Forest Resources Conservation and Ecotourism - IPB University, 1997)
There are 4 species of sea turtles in Alas Punvo National Park. The Nesting sites along south coast and east coast of this area had been disturbing by people and natural factor. The population of turtle especially in east coast Blambangan Peninsula of this national park have decrease due to the lack of management effort and this situation had been promoting turtle hunting activities of local people and fisherman at the sea illegal egg collection at the beach. To increase the population of turtle especially in east coast Blambangan Peninsula, it need the increase of control activities as management effort and build additional semi natural nesting sites in Trianggulasi and in east coast Blambangan Peninsula.Kata Kunci : Penyu, penyebaran, gmgguan, penetasan, Alas Purwo.